Hubungan antara Religiusitas dengan forgiveness pada Siswa di Madrasah Aliyah Negeri 1 Medan - Anna Wati Dewi Purba; Alfani Yudana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This istudy iaims ito isee ithe icorrelation ibetween ireligiosity iand iforgiveness iin istudents iat iMAN i1 Medan. iThe iscale iused iin ithis istudy iis ia iscale iof ireligiosity iand iscale iof iforgiveness iwhere ithe subjects iin ithis istudy iwere istudents iof iMAN i1 iMedan, itotaling i174 istudents. iThe idata ianalysis method iused iin ithis istudy iis iProduct iMoment icorrelation, iso ithe ifollowing iresults ican ibe iobtained: there iis ia isignificant ipositive icorrelation ibetween ireligiosity iand iforgiveness. iThis iresult iis evidenced by ithe icorrelation icoefficient irxy i= i0.409; iP i= i0.000 i<0.05, ithat ireligiosity icontributes ito forgiveness by i16.7%. iFrom ithese iresults iit iis iknown ithat ithere iare istill i83.3% iof iother ifactors iof iforgiveness that iare inot iexplained iin ithe istudy iand iare inot ivisible iin ithis istudy. iThat istudents ihave ihigh religiosity iwith imean iempiric i= i100.24> ihypothetical imean i= i75 iwhere ithe idifference ibetween ithe two imeans iexceeds iSD i= i7,960 iand ithe istudent's iforgiveness iis ihigh iwith imean iempiric i103.29> hypothetical imean i= i80 iwhere ithe idifference ibetween ithe itwo imeans iexceeds ithe inumber iSD i= 7,638. iFrom ithe iresults iof ithis istudy, ithe iproposed ihypothesis iis iaccepted.